IJCM_351A: A study on Internet use and its association with psychopathology of Sleep among: students at a Government Medical college in Koppal, Karnataka - Nimbannavar Smita M (Wolters Kluwer Medknow Publications, 2024)
Background: Internet addiction has become a very common disorder because of which youngsters are wasting a lot of time, becoming irritable and depressed and having poor academic/ work performance and are becoming victims of social isolation. College students have easy access to internet and so there is high chance of higher prevalence of Internet addiction among them. By studying the association of internet usage and its impact on sleep we can set boundaries for early warning signs of underlying psychopathology at the earliest. Objective: The Objectives of the study were: 1) To estimate the prevalence of Internet addiction among medical students in the study setting, 2) To estimate the prevalence of psychopathology in sleep pattern among medical students in the study setting, and 3) To determine the impact of Internet addiction on psychopathology in sleep pattern among them. Methodology: : A cross sectional study was conducted among medical students at a Government Medical college, Koppal, Karnataka for a duration of 3 months from June 2023 to August 2023. Data collection was done using a pretested and semi structured questionnaire (shared through Google form) consisting of questionnaires of Internet addiction test (IAT) to assess Internet use and Pittsburgh Sleep Quality Index (PSQI) to assess quality of sleep among them along with socio demographic and other relevant details. Statistical analysis was done using WHO Epi info software version 3.5.4. Results: The prevalence of Internet addiction among medical students was 286 (57.2%) and was found to be mild, moderate and severe in 214 (42.8%), 68 (13.6%) and 4 (0.8%) of students respectively. Quality of sleep was disturbed in 270 (54%) of students according to PSQI. The study found significant association between Internet addiction among medical students and quality of sleep among them Conclusion: Need for Behavior change communication strategies to reduce unnecessary use of Internet.